2009
DOI: 10.1177/0145482x0910301008
|View full text |Cite
|
Sign up to set email alerts
|

Hand Movements and Braille Reading Efficiency: Data from the Alphabetic Braille and Contracted Braille Study

Abstract: Using a subset of data from the Alphabetic Braille and Contracted Braille Study, researchers analyzed the patterns and characteristics of hand movements as predictors of reading performance. Statistically significant differences were found between one- and two-handed readers and between patterns of hand movements and reading rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 7 publications
3
25
1
1
Order By: Relevance
“…We show that most sighted adults can learn whole-word braille reading, given the right method and motivation. The pace of braille acquisition in our sighted subjects was comparable to that of blind children learning braille reading in school [ 27 – 29 ]. Thus, our results might suggest that experience-dependent mechanisms largely account for the blind’s mastery in complex tactile tasks.…”
Section: Introductionmentioning
confidence: 77%
“…We show that most sighted adults can learn whole-word braille reading, given the right method and motivation. The pace of braille acquisition in our sighted subjects was comparable to that of blind children learning braille reading in school [ 27 – 29 ]. Thus, our results might suggest that experience-dependent mechanisms largely account for the blind’s mastery in complex tactile tasks.…”
Section: Introductionmentioning
confidence: 77%
“…Reading rates of children who read braille are and have been of major concern in the research literature (e.g., Nolan & Kederis, 1969;Wall Emerson, Holbrook, & D'Andrea, 2009). This research has documented that reading rates of braille readers are approximately half or less of the speed of their age-matched, sighted peers (Lusk & Corn, 2006;Wall Emerson et al, 2009;Wright, Wormsley, & Kamei-Hannan, 2009). Researchers have also described disparities between the reading comprehension ability and chronological age of students who read braille (Dodd & Conn, 2000;Wall Emerson et al, 2009).…”
Section: Braille Readingmentioning
confidence: 99%
“…Other research suggests that reading braille with a twohanded pattern is associated with higher proficiency in reading than reading braille with one hand (Kusajima, 1974;Wright et al, 2009). There may not have been enough participants reading with a one-handed pattern to find a significant association between hand movements and comprehension.…”
Section: Interaction Of Braille and Word Identification Processesmentioning
confidence: 99%
“…Later research has confirmed these early notions [26,27] and added many linguistic aspects of the text as possible causes [28, 23, 2930]. Indeed, linguistic manipulations of the text can have the same effect on reading braille and increase the likelihood of regressive hand movements [31, 17, 3235]. The kinematic properties of reading hand movements and regressive hand movements are not qualitatively different [36].…”
Section: Introductionmentioning
confidence: 99%